2016
DOI: 10.18869/acadpub.cmm.2.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus species in indoor environments and their possible occupational and public health hazards

Abstract: The genus Aspergillus, which consists of a few hundred opportunistic mold species found in various climatic conditions, causes diseases including localized infections, fatal diseases, allergic responses, and inhaled conidia in humans. Herein, we present an overview of the most common diseases and allergic infections caused by Aspergillus species and their associated health hazards in various indoor environments worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 64 publications
2
103
0
Order By: Relevance
“…These findings are in accordance with the results of Nwakanma et al (2016). The previous findings revealed that fungal endophytes belonging to Aspergillus (Mousavi et al, 2016) and Penicillium (Chowdhary et al, 2016) genus have shown antibacterial activity. Our study has also shown that T. longibrachiatum MD33 also contained compounds that were active against plant bacterial pathogens and rhizosphere soilcontaminated (wastewater) pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with the results of Nwakanma et al (2016). The previous findings revealed that fungal endophytes belonging to Aspergillus (Mousavi et al, 2016) and Penicillium (Chowdhary et al, 2016) genus have shown antibacterial activity. Our study has also shown that T. longibrachiatum MD33 also contained compounds that were active against plant bacterial pathogens and rhizosphere soilcontaminated (wastewater) pathogenic microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…In which this leads to furuncles (boils) and carbuncles (a collection of furuncles). Deeply penetrating S. aureus infections can be severe, its most commonly seen in wounds, pneumonia, bacteremia [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is now the most frequent cause of nosocomial infections, at a rate about as high as that due to its more virulent cousin Staphylococcus aureus. Interestingly, many of these determinants are believed to have original functions in the non-infectious lifestyle of this microorganism, emphasizing the accidental nature of S. epidermidis infections [12].…”
Section: Staphylococcus Epidermidis;mentioning
confidence: 99%
“…Aflatoxin is a secondary metabolite of A. flavus, and its biosynthesis is strongly influenced by various environmental factors [55]. Contamination of crops, such as cotton, peanuts, maize, and tree nuts by aflatoxin creates a substantial food safety risk, especially in developing countries [56]. Researchers used KEGG pathway analysis to investigate the expression levels of some proteins in A. flavus and demonstrated that the degradation of valine, leucine, and isoleucine in solid media can increase the synthesis of acyl-CoA compared to that in liquid media.…”
Section: The Function Of Acbp From Aspergillus Flavus (A Flavus) Maymentioning
confidence: 99%